High‐Performance Flexible Thermoelectric Devices Based on All‐Inorganic Hybrid Films for Harvesting Low‐Grade Heat - Wu, Bo; Guo, Yang; Hou, Chengyi; Zhang, Qinghong; Li, Yaogang; Wang, Hongzhi (Advanced functional materials, 2019)
The fabrication of a flexible thermoelectric (TE) device that contains flexible, all‐inorganic hybrid thin films (p‐type single‐wall carbon nanotubes (SWCNTs)/Sb2Te3 and n‐type reduced graphene oxide (RGO)/Bi2Te3) is reported. The optimized power factors of the p‐type and n‐type hybrid thin films at ambient temperature are about 55 and 108 µW m−1 K−2, respectively. The high performance of these films that are fabricated through the combination of vacuum filtration and annealing can be attributed to their planar orientation and network structure. In addition, a TE device, with 10 couples of legs, shows an output power of 23.6 µW at a temperature gradient of 70 K. A prototype of an integrated photovoltaic‐TE (PV‐TE) device demonstrates the ability to harvest low‐grade “waste” thermal energy from the human body and solar irradiation. The flexible TE and PV‐TE device have great potential in wearable energy harvesting and management. A flexible thermoelectric generator based on all‐inorganic hybrid films of n‐type RGO/Bi2Te3 and p‐type SWCNTs/Sb2Te3 is fabricated. The prototypes of a wearable wrist band and a photovoltaic–thermoelectric integrated device are proven, which can be used for harvesting waste heat and stabilizing the photovoltaic performance.